Reputation: 323
I have a task that's driving me crazy because i have no clue where to start.
The task is the following: Convert the given boolean expression so that it only contains NAND operations and no negations.
c * b * a + /c * b * /a
I assume that it's possible, :D but i have no idea how to do it and spent several hours just for spinning in circles.
Could someone please point me in the right direction?
Best regards,
askin
Update:
thanks to the answers I think I found the solution:
c*b*a = /(/(c*b*a)*/(c*b*a)) = A;
/c*b*/a = /(/(/(a*a)*b*/(c*c))*/(/(a*a)*b*/(c*c))) = B;
c*b*a+/c*b*/a = A + B = /(/(A*A)*/(B*B))
Upvotes: 4
Views: 62901
Reputation: 9606
c * b * a + /c * b * /a
only NAND
/( /(c * b * a) * /( /(c * c) * b * /(a * a) ) )
NAND( NAND(c,b,a) , NAND( NAND(c,c), b, NAND (a, a)))
So you need, two 3 gate NAND, three 2 gate NAND.
NOT (A) = NAND (A,A)
A OR B = NAND (NAND (A, A), NAND(B, B))
Upvotes: 1
Reputation: 30775
For a good in-depth discussion of how to build boolean expressions with only one kind of function/logic gate (in this case, NOR, but changing it to NAND is straightforward), have a look at
The Pragmatic Programmer Magazine 2012-03: The NOR Machine
Upvotes: 1
Reputation: 8586
This has a breakdown of how to build other logic gates via NAND. Should be a straightforward application:
http://en.wikipedia.org/wiki/NAND_logic
E.g. C = A AND B is equivalent to
C = NOT (A NAND B)
or
C' = (A NAND B)
C = C' NAND C' (effectively NOT'ing A NAND B)
Upvotes: 2